Brief exposure of embryos to steroids or aromatase inhibitor induces sex reversal in Nile tilapia (Oreochromis niloticus). Issue 1 (5th November 2014) - Gennotte, Vincent; Mafwila Kinkela, Patrick; Ulysse, Bernard; Akian Djétouan, Dieudonné; Bere Sompagnimdi, Frédéric; Tomson, Thomas; Mélard, Charles; Rougeot, Carole
ABSTRACT This study aimed to develop sex reversal procedures targeting the embryonic period as tools to study the early steps of sex differentiation in Nile tilapia with XX, XY, and YY sexual genotypes. XX eggs were exposed to masculinizing treatments with androgens (17α‐methyltestosterone, 11‐ketotestosterone) or aromatase inhibitor (Fadrozole), whereas XY and YY eggs were subjected to feminizing treatments with estrogen analog (17α‐ethynylestradiol). All treatments consisted of a single or double 4‐hr immersion applied between 1 and 36 hour post‐fertilization (hpf). Concentrations of active substances were 1000 or 2000 μg l−1 in XX and XY, and 2000 or 6500 μg l−1 in YY. Masculinizing treatments of XX embryos achieved a maximal sex reversal rate of 10% with an exposure at 24 hpf to 1000 μg l−1 of 11‐ketotestosterone or to 2000 μg l−1 of Fadrozole. Feminization of XY embryos was more efficient and induced up to 91% sex reversal with an exposure to 2000 μg l−1 of 17α‐ethynylestradiol. Interestingly, similar treatments failed to reverse YY fish to females, suggesting either that a sex determinant linked to the Y chromosome prevents the female pathway when present in two copies, or that a gene present on the X chromosome is needed for the development of a female phenotype. J. Exp. Zool. 323A: 31–38, 2015. © 2014 Wiley Periodicals, Inc.